Association between Antimicrobial Peptide Histatin 5 Levels and Prevalence of Candida in Saliva of Patients with Down Syndrome - Tomoko Komatsu; Kiyoko Watanabe; Nobushiro Hamada; Eva Helmerhorst; Frank Oppenheim; Masaichi Chang-il Lee (MDPI AG, 2021)
There are no studies on Candida colonization and micropeptides of saliva in any patient. Therefore, we studied the effects of the salivary antimicrobial peptide histatin 5 on oral fungal colonization; subjects were subdivided into Down syndrome (D) and normal (N) groups by age: N-1 and D-1, age <20 years; N-2 and D-2, age >40 years. Histatin 5 concentration in saliva was measured by enzyme-linked immunosorbent assay. Oral Candida species were identified using CHROMagar Candida. Candida colonization was significantly enhanced in the D-1 and D-2 groups compared to the N-1 and N-2 groups. There was no predominant difference in salivary histatin 5 concentration between the D-1 and N-1 groups, but it was significantly lower in the D-2 group than in the N-2 group. Only in the N-2 group was there a correlation between the concentration of histatin 5 and total protein, while no correlation was found in the other groups. In elderly patients with Down syndrome, the decrease in histatin 5 shown in this study may lead to oral Candida colony formation. Therefore, the results of this study suggest that a deficiency of the antimicrobial peptide histatin 5 could possibly induce oral Candida infection in DS.